2020
DOI: 10.22541/au.159136821.11895818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into ventricular arrhythmogenesis of hydroxychloroquine and azithromycin for the treatment of COVID-19

Abstract: Background and Purpose: We investigate mechanisms for potential pro-arrhythmic effects of hydroxychloroquine (HCQ) alone, or combined with azithromycin (AZM), in Covid-19 management supplementing the limited available experimental cardiac safety data. Experimental Approach: We integrated patch-clamp studies utilizing In Vitro ProArrhythmia Assay Schema IC50 paradigms, molecular modelling, cardiac multi-electrode array and voltage (RH237) mapping, ECG studies, and Ca2+ (Rhod-2 AM) mapping in isolated Langendorf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Besides the reduced cell viability, treatment with 10 µM HCQ resulted in a progressive increase in FPDc, CV and beating frequency in iPSC-CMs during the 7-day treatment. The increased FPDc was also reported in the guinea pig heart upon acute treatment with 10 µM HCQ alone ex vivo 16 . In our study, we observed a slight reduction of FPDc in iPSC-CMs after the 7-day treatment with 10 µM AZM alone, while CV was increased to a similar extend as in cells treated with 10 µM HCQ.…”
Section: Hcq and Azm Differentially Affect Ipsc-cm Viability And Functionalitysupporting
confidence: 64%
See 3 more Smart Citations
“…Besides the reduced cell viability, treatment with 10 µM HCQ resulted in a progressive increase in FPDc, CV and beating frequency in iPSC-CMs during the 7-day treatment. The increased FPDc was also reported in the guinea pig heart upon acute treatment with 10 µM HCQ alone ex vivo 16 . In our study, we observed a slight reduction of FPDc in iPSC-CMs after the 7-day treatment with 10 µM AZM alone, while CV was increased to a similar extend as in cells treated with 10 µM HCQ.…”
Section: Hcq and Azm Differentially Affect Ipsc-cm Viability And Functionalitysupporting
confidence: 64%
“…As MEA-measurements and video-based motion analysis allow frequent documentation of iPSC-CM function during 7 days of drug treatment, our study provides first evidence for the functional consequences of AZM and HCQ under long-term treatment, whereas insights from previous studies are limited to acute or short-term treatment 16 . We show that both AZM and HCQ negatively affect the viability, morphology, sarcomeric structure as well as the contractile and electrophysiological function of iPSC-CMs at clinically relevant concentrations and treatment duration.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Hydroxychloroquine, and to a lesser extent AZM, blocks the IKr current and their combination has a greater effect 57 . In addition, AZM also increases peak and late sodium current, thereby further delaying cardiac repolarization 58 .…”
Section: Current Efforts At Repurposing Cq and Hcq For Covid‐19 Infecmentioning
confidence: 99%